2019
DOI: 10.3390/w11112213
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Inorganic Geogenic Phosphorus Load to a Groundwater-Fed Lake: Implications of Terrestrial Phosphorus Cycling by Groundwater

Abstract: The general perception has long been that lake eutrophication is driven by anthropogenic sources of phosphorus (P) and that P is immobile in the subsurface and in aquifers. Combined investigation of the current water and P budgets of a 70 ha lake (Nørresø, Fyn, Denmark) in a clayey till-dominated landscape and of the lake’s Holocene trophic history demonstrates a potential significance of geogenic (natural) groundwater-borne P. Nørresø receives water from nine streams, a groundwater-fed spring located on a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
(75 reference statements)
0
25
0
Order By: Relevance
“…Moreover, 15 out of 20 research papers in this Special Issue have a purely hydrological focus, while only five consider hydrological and biogeochemical interactions. In fact, only two contributions (both by Nisbeth et al [13,14]) focus on mass transport between groundwater and surface water by determining groundwater-borne phosphorus loads to a lake. This could be due to the challenging complexity of groundwater-surface water exchange processes alone, because the investigation of related mass fluxes adds to further complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 15 out of 20 research papers in this Special Issue have a purely hydrological focus, while only five consider hydrological and biogeochemical interactions. In fact, only two contributions (both by Nisbeth et al [13,14]) focus on mass transport between groundwater and surface water by determining groundwater-borne phosphorus loads to a lake. This could be due to the challenging complexity of groundwater-surface water exchange processes alone, because the investigation of related mass fluxes adds to further complexity.…”
Section: Discussionmentioning
confidence: 99%
“…They sampled precipitation, lake water, river water, and groundwater for chloride concentrations and water-stable isotopes to delineate discharge and recharge areas for the dry (cold) and the wet season in the complex hydrogeological environment of Lake Hulun. Nisbeth et al [13,14] found that geogenic P might be a much more important P source in some instances than is generally assumed. Their study contributes to the still-overlooked problem of LGD-induced lake eutrophication [24,[28][29][30].…”
Section: Groundwater-lake Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination and interrelated environmental elements such as increasing population, climate change, land use change, and pollution have resulted in the scarcity of high quality water for human use and ecosystem sustainability [3,4]. Increasing urban demand for water is not only due to increasing urban population, but also to aging and inadequate infrastructure that can be addressed to some extent They stated that the primary pollutant in their study was phosphate, which is supported by other studies [9].…”
Section: Introductionmentioning
confidence: 56%
“…Nine small streams discharge into the lake (Figure 1b), numbered 1 to 9 in order of decreasing annual P loading to the lake. This numbering was based on the relative size of the annual dissolved inorganic P (DIP)-flux quantified by Nisbeth et al [48]. Stream 1 and the spring on Lucieø both represent anoxic groundwater discharging from a regional confined aquifer, with geogenic P and ferrous iron concentrations of~150 µg P/L and 1700 µg Fe/L, respectively [49].…”
Section: Study Sitementioning
confidence: 99%